Nematoides e fungos entomopatogênicos no controle de Dalbulus maidis (Delong & Wolcott) e seletividade de produtos fitossanitários registrados para a cultura do milho - Oliveira, Ana Carolina de (2024)
Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Cicadellidae), constitutes an important phytosanitary threat to corn crops, due to the transmission of the stunt complex and the fine streak and striate mosaic viruses, in addition to the suction of photoassimilates, affecting corn production. The pest is present throughout the crop cycle, however corn is more sensitive to attack in its initial stages, high temperatures favor an increase in the population, losses can reach 100% of crops with high infestation. To control this pest, rural producers use chemical insecticides, however this method has low efficiency and can select resistant individuals. Fungi are the most studied entomopathogens, Beauveria, Cordyceps and Metarhizium are the main genera studied and with several bioinsecticides formulated and commercialized , another little studied but promising group are the entomopathogenic nematodes that have bacteria inside them, since the entomopathogenic nematode penetrates the insect through the natural openings, the bacteria are released into the insect's hemolymph, causing its death, Heterorhabditis and Steinernema are the genera commonly studied and used as biocontrol. The present study evaluated the efficiency of isolates of entomopathogenic fungi and nematodes in controlling D. maidis under laboratory conditions, as well as the lethal concentration of the isolates and selectivity testing with chemicals registered in corn crops. There was no significant difference between the Heterorhabditis and Steinernema isolates tested, and they presented mortality rates greater than 50%. The fungal isolate Metarhizium sp. IDM 1-1 had a mortality rate greater than 70%. Regarding the lethal concentration (LC50), the highest mortality was observed at the concentration 75 infective juveniles (Jis) adult-1 for H. amazonensis MC01 and 25 JIs adult-1 for S. feltiae IBCB 47. There was no significant difference between the concentrations tested from isolates Beauveria sp. 9 and Metarhizium sp. IDM 1-1. All insecticides and herbicides negatively affected the isolate H. amazonensis MC01 and only the herbicide tembotrione was classified as harmless to S. feltiae IBCB 47. The mycelial growth of the Beauveria sp. 9 and Metarhizium sp. IDM 1-1 were significantly affected, the insecticides deltamethrin and methomyl reduced the mycelial growth of the isolate Beauveria sp. 9, regarding the isolate Metarhizium sp. IDM 1-1, all insecticides tested affected their mycelial growth.